DAYALENTING SEKTOR PARIWISATA DESA WISATA PENTINGSARI AKIBAT MULTIBENCANA - DEWI, MARTHA KURNIA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Pentingsari Tourism Village is a tourist destination in Sleman . This tourism village suffered a catastrophic impact of Merapi Eruption in 2010 and Gale in 2012. The tourism loss assessment is done to see how far the impact of tourism caused by multidisaster events. After the calculation, we performed an analysis of the process of resilience and identification of tourism resilience factor. It is useful to know how a community with its tourism sector can recover from a disaster. In addition, it can also give a look for other factors that play a role in tourism resilience. Loss assessment is done with Damage and Loss Assessment Method or DaLA. The method use the two approaches, damage and loss. Damage derived from the value of the asset repair damaged tourism, while loss refers to the loss of revenue due to the closing effect of the tourist village after the eruption. The recovery process approach is using roles of resilience in determining community response to a hazard eventâ. In this approach, the analysis is conducted from the disaster, the initial post- disaster conditions, and the start of the resilience until the resilience process is completed. Meanwhile, the resilience is assessed by looking at the condition of the first tourist visits until tourist traffic back to normal, and post-disaster resilience infrastructure. Meanwhile, to identificate the resilience factors we use a tool \" relationship between capital domains and community disaster resilience \" through indicators of social capital, economic, human resources, physical and natural. Eruption caused a loss of Rp Rp.406.660.000,-. It is also accompanied by damage to infrastructure, homestay and attractions. Gale in 2012, causing a loss of Rp.52.850.000, and damage to some homestay. The resilience process after the eruption began when the residents returned from refugee at the end of the year. At first visit, tourism resilience has not been completed. Tourism resilience finish at the end of 2011 that is when the visit and activities are returning to normal. However, resilience of infrastructure is completed at the end of 2013. And at the end of 2013, tourist arrivals were higher than before the disaster occurred. Post-gale resilience is faster than the resilience of eruption. That afternoon, after the gale struck, residents helped volunteers to do the cleaning on the trees which collapsed. Factors that affect resilience is the confidence of customers to come back, and strong network with multiple parties. Personal assets belonging to people is also used for resilience. Promotion ability, public disclosure, the involvement of the whole community to develop tourism, natural resources owned, construction of infrastructure such as roads and bridges, some help from the government, NGOs, universities, relations, and tourist are other factors that encourage resilience in Pentingsari.